1984
DOI: 10.1002/app.1984.070290532
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of poly(ϵ‐caprolactone) (PCL) and poly(styrene‐co‐acrylonitrile) (SAN) blends. II. The influence of the AN content in SAN copolymer upon blend compatibility

Abstract: SynopsisThe compatibility of polymer blends of poly(c-caprolactone) (PCL) and poly(styrene-co-acrylonitrile) (SAN) containing various acrylonitrile (AN) contents was studied to evaluate the influences of copolymer composition and PCL concentration upon blend compatibility. Blend compatibility was characterized by the occurrence of a single glass transition intermediate between the transitions of the respective pure components. The glass transitions were determined by differential scanning calorimetry (DSC) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
0
2

Year Published

1986
1986
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 17 publications
5
60
0
2
Order By: Relevance
“…For example, Janarthanan et al (1993) have used Fourier transform infrared spectroscopy to detect intramolecular interaction in blends of poly(ecapro1actone) and poly(styrene-co-acrylonitrile). This system displays a miscibility window as a function of copolymer composition (Chiu and Smith, 1984). The shift of the y-CH outof-plane deformation band of styrene to higher frequencies shows that miscibility in this system is mainly due to the dilution of the unfavorable intramolecular interaction between styrene and acrylonitrile segments by poly(&-caprolactone).…”
Section: Introductionmentioning
confidence: 90%
“…For example, Janarthanan et al (1993) have used Fourier transform infrared spectroscopy to detect intramolecular interaction in blends of poly(ecapro1actone) and poly(styrene-co-acrylonitrile). This system displays a miscibility window as a function of copolymer composition (Chiu and Smith, 1984). The shift of the y-CH outof-plane deformation band of styrene to higher frequencies shows that miscibility in this system is mainly due to the dilution of the unfavorable intramolecular interaction between styrene and acrylonitrile segments by poly(&-caprolactone).…”
Section: Introductionmentioning
confidence: 90%
“…[14] Numerous studies have been carried out to modify PCL by blending or co-polymerization with other polymers. [15][16][17][18][19][20][21][22][23][24][25] In the case of PCL/SAN blend, the miscibility of this system and the influence of acrylonitrile (AN) content in the copolymer upon blend miscibility have been studied by Chiu et al [20] They found that SAN and PCL are miscible when the AN content in SAN ranges from 8 to 28 wt.-%. Savoboda et al [21,22] studied the morphology of PCL/SAN blend via competition with spinodal decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is very imethylene-propylene-diene terpolymer. portant for the development of rubber-modified SAN can readily blend with a number of other polymers to find how to improve the impact polymers including poly(1-caprolactone), 3,4 polystrength without deterioration of the other propcarbonate, [5][6][7][8][9] poly(vinylidenefluoride), 10 nylon, …”
Section: Introductionmentioning
confidence: 99%